Clinical and Laboratory Findings of COVID-19 in High-Altitude Inhabitants of Saudi Arabia - Abdelsalam, Mostafa; Althaqafi, Raad M. M.; Assiri, Sara A.; Althagafi, Taghreed M.; Althagafi, Saleh M.; Fouda, Ahmed Y.; Ramadan, Ahmed; Rabah, Mohammed; Ahmed, Reham M.; Ibrahim, Zein S.; Nemenqani, Dalal M.; Alghamdi, Ahmed N.; et al. (Frontiers in Medicine, 2021)
Background: SARS-CoV-2, the causative agent of COVID-19, continues to cause a worldwide pandemic, with more than 100 million being affected globally as of this writing. People’s responses to COVID-19 range from asymptomatic to severe, and the disease is sometimes fatal. Its severity is affected by different factors and comorbidities of the infected patients. Living at a high altitude could be another factor that affects the severity of the disease in infected patients. Methods: In the present study, we have analyzed the clinical, laboratory, and radiological findings of COVID-19 infected patients in Taif, a high altitude region of Saudi Arabia. In addition, we compared matched diseased subjects to those living at sea level. We hypothesized that people living in high altitude locations are prone to develop a more severe form of COVID-19 than those living at sea level. Results: Age and a high Charlson comorbidity score were associated with increased numbers of intensive care unit (ICU) admissions and mortality among COVID-19 patients. These ICU admissions and fatalities were found mainly in patients with comorbidities. Rates of leukocytosis, neutrophilia, higher D-dimer, ferritin, and highly sensitive C-reactive protein (CRP) were significantly higher in ICU patients. CRP was the most independent of the laboratory biomarkers found to be potential predictors of death. COVID-19 patients who live at higher altitude developed a less severe form of the disease, and had a lower mortality rate, in comparison to matched subjects living at sea level. Conclusion: CRP and Charlson comorbidity scores can be considered predictive of disease severity. People living at higher altitudes developed less severe forms of COVID-19 disease than those living at sea level, due to a not-yet-known mechanism.